A Case of Intracranial Solitary Fibrous Tumor/Hemangiopericytoma Repeatedly Misdiagnosed as Hypertensive Intracerebral Hemorrhage - Eom, Ki Seong; Kim, Hun-Soo (Brain tumor research and treatment, 2020)
Because solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) contain identical genetic abnormalities, the World Health Organization coined the term SFT/HPC to describe these lesions. Here, we present a rare case of SFT/HPC in a 40-year-old man with massive repeated intracranial hemorrhage (ICH) in right medial temporal lobe. ICHs from a SFT/HPC were repeatedly misdiagnosed as hypertensive ICH by several departments and hospitals over approximately eight months, and the patient underwent inappropriate treatments. The amount of repeated ICH accompanying the tumor has increased significantly compared to the first ICH, which may suggest rapid tumor growth. To avoid misdiagnosis and inappropriate treatment, surgeons should carefully examine all past and current patient-related radiological images and medical records before considering surgery.Because solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) contain identical genetic abnormalities, the World Health Organization coined the term SFT/HPC to describe these lesions. Here, we present a rare case of SFT/HPC in a 40-year-old man with massive repeated intracranial hemorrhage (ICH) in right medial temporal lobe. ICHs from a SFT/HPC were repeatedly misdiagnosed as hypertensive ICH by several departments and hospitals over approximately eight months, and the patient underwent inappropriate treatments. The amount of repeated ICH accompanying the tumor has increased significantly compared to the first ICH, which may suggest rapid tumor growth. To avoid misdiagnosis and inappropriate treatment, surgeons should carefully examine all past and current patient-related radiological images and medical records before considering surgery.